Diagnostic Accuracy of Ultrasonography in the Detection of Postsurgical Recurrence in Crohn’s Disease: A Systematic Review with Meta-analysis - Antonio Rispo; Nicola Imperatore; Anna Testa; Olga Maria Nardone; Gaetano Luglio; Nicola Caporaso; Fabiana Castiglione (2018)
The postoperative course of Crohn's disease (CD) is best predicted by ileocolonoscopy. Ultrasonography (US) has been proposed as indicator for postsurgical recurrence (PSR), but further confirmation is needed. We performed a systemic review with meta-analysis to assess the pooled diagnostic accuracy of US in the evaluation of PSR. The systematic review was performed in PubMed/MEDLINE, EMBASE, SCOPUS, and Cochrane databases to identify studies assessing the US accuracy in PSR diagnosis. A sub-analysis between bowel sonography (BS), small-intestine contrast ultrasound (SICUS), and contrast-enhanced ultrasound (CEUS) was performed. Pooling was performed using diagnostic fixed or random-effect model according with heterogeneity. Ten studies (536 patients) met the inclusion criteria. There was no publication bias. Pooled sensitivity and specificity of US in detecting PSR were 0.94 (95% CI, 0.86–0.97) and 0.84 (95% CI, 0.62–0.94; diagnostic accuracy 90%), respectively. At sub-analysis, pooled sensitivity and specificity were 0.82 (95% CI, 0.76–0.88) and 0.88 (95% CI, 0.74–0.95) respectively for BS, with 0.99 (95% CI, 0.99–1.00) and 0.74 (95% CI, 0.73–0.74) for SICUS. Finally, an SROC curve was built to establish the best bowel wall thickness (BWT) cutoff able to predict the presence of severe PSR (Rutgeerts ≥3): a BWT ≥5.5 mm at US revealed sensitivity of 83.8% (95% CI, 73.6%–90.6%), specificity of 97.7% (95% CI, 93%–99%). US shows high sensitivity and specificity for the diagnosis of PSR. SICUS appears more sensitive—but less specific—than BS, while the role of CEUS needs further investigation. A cutoff value of BWT ≥5.5 mm is strongly indicative of severe PSR.